'We handle it, I guess you'd say, the East Texas way': Place-based effects on the police decision-making process and non-arrest outcomes. (2nd January 2023) - Peterson, Jessica Rene
ABSTRACT: Informal law enforcement approaches to crime problems are largely hidden from the public domain. Non-urban communities are often absent from the literature on police decision-making, but many characteristics of 'the rural' – such as lack of supervision, diminished access to resources, and more – expand police discretion and increase the use of informal policing methods. While most research on police discretion focuses on the decision to arrest, the current study utilizes semi-structured focused interviews with law enforcement officers in rural Texas to address non-arrest decision-making and the informal policing of youth. Specific informal responses, as well as factors that influence officer decision-making, are discussed. The findings suggest that the structural, cultural, and situational context of a rural setting uniquely affects police decision-making, highlighting the significance of geographic and sociocultural environment in use of discretion. The qualitative approach and analysis provide extensive detail regarding place-based effects on the police decision-making process, including officer motivations and how officers attribute meaning and contextually filter information in an encounter with youth. By illuminating the gray area of policing, these findings have implications for rural law enforcement training and practices and provide future direction for broader agency policy research.